Phytochemical screening and purification of n-hexane fraction of Calophyllum soulattri leaves - Sunarto, Sunarto; Yuliasari, Agnes; Susilowati, Sri Sutji; Wasito, Hendri; Wijaya, Triyadi Hendra; Fareza, Muhamad Salman (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2022)
Background: Calophyllum soulattri Burm F. is widely utilized in traditional medicine. It is necessary to identify secondary metabolites from C. soulattri leaves to determine the pharmacologically active chemicals. Objective: This study aimed to screen the phytochemical content and purify the n-hexane fraction of C. soulattri leaves from Banyumas, Indonesia. Methods: The n-hexane fraction was macerated with methanol, followed by liquid-liquid fractionation with n-hexane. The n-hexane fraction was tested for flavonoids, triterpenoids/steroids, saponins, and phenols using the test tube method. In addition, the compounds were purified using column chromatography. The purified compound was identified by the Liebermann-Burchard reagent, which was compared with commercially available steroid drugs as reference. Results: Phytochemical analysis revealed that the n-hexane fraction of C. soulattri leaves contained secondary metabolites such as flavonoid, steroid, and phenol compounds. Analyses with the Liebermann-Burchard reagent indicated that the purified compound was potentially a steroid. Conclusion: The compound extracted from the n-hexane fraction of C. soulattri leaves was expected as a steroid.